Alkali Pozzolan Cement for Integral Sustainability - Kulasuriya, Chandana (Curtin University, 2015)
This thesis presents the design and development of an alternative cement called ‘Alkali Pozzolan Cement’ (APC) for ‘integral sustainability’. The term ‘integral sustainability’ is a philosophical concept that implies an integration of not only the aspects related to ecological sustainability, but also those of technological, economic and social sustainability. Accordingly, this research can be considered as engineering as well as philosophical research; hence, mixed research methods were adopted to achieve the research objectives.